Cholera El Tor enteritis in Jakarta - Jeni Iswandari; Helena Erawan; S. Komalarini; Shinta Njotosiswojo (Indonesian Pediatric Society, 1973)
Gastrointestinal disturbances with symptoms of vomiting and diarrhoea, accompanied with acute dehydration, acidosis, sodium and potassium losses broke out in 1920 in Asia. This disease was called cholera Asiatica or classical cholera and was caused by